Game phases performance in men's volleyball: from initial to top-level categories. [Rendimiento de las fases de juego en voleibol masculino: desde la iniciación hasta las categorías de alto rendimiento]. - Antonio Garcia de Alcaraz; Enrique Ortega; José Manuel Palao (Ramón Cantó Alcaraz, 2020)
This study aimed to analyze the evolution of the game phases performance and the way of scoring points throughout different age groups and levels of competition in male volleyball. The sample was 53,320 game phases performed in 299 sets from five competition categories (national under-14, national under-16, national under-19, senior national and senior international). An observational design was used. The variables were: competition category, game phase performance, and way that points were scored. The higher the category, the higher the points in attack and side-out phase (from 48.37% -U14- to 69.61% -senior international-) and the lower points by the serving team (from 51.63% -U14- to 30.39% -senior international-). The opponent errors decreased as move to higher categories. The greater differences were observed between initial stages (under-14, under-16, and under-19) and senior categories. The cause of these results is related to the increase of the points scored by the attack in the side-out phase. The contributions of the different actions change through the developmental process from initial to top-level categories. This information may be useful to understand the technical-tactical training progression and to evaluate the long term athlete development of male volleyball players.